Handbook for Liturgical Studies, Volume III : The Eucharist - Chupungco, Anscar J. (Book collections on Project MUSE., 1999)
Volume III: The Eucharist contributes to the reflection on the meaning and purpose of the Eucharistic celebration. It also offers to teachers and students of liturgy a handbook for studying this subject according to a system based on historical development, theology and doctrine, liturgical texts and traditions in both East and West, and pastoral considerations.